Determinants of Behavior Intention and Use Behavior among Bukalapak’s Consumers - Giandi, Oxsy; Irawan, Isa; Ambarwati, Rita (IPTEK The Journal for Technology and Science, 2020)
The development of communication and information technology has touched the marketing and sales industry. In recent years, there have been many market places in Indonesia, where people buy and sell without meeting face to face. This study investigates the influence of people's intention on the use of behavior to buy at the market place in Indonesia. The market, which becomes the research object is Bukapalak. The data were obtained using the questionnaire. This study obtained 210 respondents, and the data were processed by the method of partial least square. There is a positive and significant influence of behavioral intention from Bukalapak’s consumer on the use (usage) behavior. The dominant determinant indicator in this study is the degree of the purpose of using the market place.